5x-3=-4+3

Simple and best practice solution for 5x-3=-4+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3=-4+3 equation:


Simplifying
5x + -3 = -4 + 3

Reorder the terms:
-3 + 5x = -4 + 3

Combine like terms: -4 + 3 = -1
-3 + 5x = -1

Solving
-3 + 5x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 5x = -1 + 3

Combine like terms: -3 + 3 = 0
0 + 5x = -1 + 3
5x = -1 + 3

Combine like terms: -1 + 3 = 2
5x = 2

Divide each side by '5'.
x = 0.4

Simplifying
x = 0.4

See similar equations:

| f(x)=(x^4-32x^3)(4x^2-x) | | 372=-0.5x^2+36x-150 | | 15-(-3)(-x+8)-3= | | 5/2-2x=6/4 | | 3(2x-1)-4(3x-5)=-7 | | 65x+45=50x+30 | | -2+4(5x+2)= | | 32x-.21x=195+12x | | cos(x)+cos(2x)=-1 | | y^2+12y+36=r | | g(-3)=2x^3+2 | | -2x+10=3x+45 | | -2*25+2y=44 | | c/4=1`6 | | 0.03(y-7)+0.14y=0.07y-0.20 | | 9x(2x-4)= | | 3x-9y=-21 | | 13=1-13 | | 27x+14=3(9x-7) | | 2e-8=14# | | -5(6x-4)= | | 6f=-5x+2 | | Y-5x=-8 | | 2x^2+5=-32 | | (-35)x(-14)x(0.5)= | | -81-4(7-3x)=13(x-8) | | 84-48/8 | | .25t+9=3 | | 2x-10x=30 | | (4x-9)(10x+5)=0 | | f(x)=-5x^2+2x-1 | | x^2-4x/x |

Equations solver categories